Transient Receptor Potential Channels, Natriuretic Peptides, and Angiotensin Receptor-Neprilysin Inhibitors in Patients With Heart Failure - Ding, Kun; Gui, Yang; Hou, Xu; Ye, Lifang; Wang, Lihong (Frontiers in Cardiovascular Medicine, 2022)
Heart failure (HF) remains the leading cause of death, morbidity, and medical expenses worldwide. Treatments for HF with reduced ejection fraction have progressed in recent years; however, acute decompensated heart failure remains difficult to treat. The transient receptor potential (TRP) channel family plays roles in various cardiovascular diseases, responding to neurohormonal and mechanical load stimulation. Thus, TRP channels are promising targets for drug discovery, and many studies have evaluated the roles of TRP channels expressed on pain neurons. The natriuretic peptide (NP) family of proteins regulates blood volume, natriuresis, and vasodilation and can antagonize the renin-angiotensin-aldosterone system and participate in the pathogenesis of major cardiovascular diseases, such as HF, coronary atherosclerotic heart disease, and left ventricular hypertrophy. NPs are degraded by neprilysin, and the blood level of NPs has predictive value in the diagnosis and prognostic stratification of HF. In this review, we discuss the relationships between typical TRP family channels (e.g., transient receptor potential cation channel subfamily V member 1 andTRPV1, transient receptor potential cation channel subfamily C member 6) and the NP system (e.g., atrial NP, B-type NP, and C-type NP) and their respective roles in HF. We also discuss novel drugs introduced for the treatment of HF.